Bronchopulmonary Actinomycosis: A Lung Disease of Diagnostic Dilemma - Chowdhury, Md. Abir Tazim; Magdum, Munama (Emerging Trends in Disease and Health Research Vol. 9, 2022)
This chapter will discuss bronchopulmonary actinomycosis and our clinical recommendation with the literature review. Actinomycosis is a disease caused by filamentous Gram-positive anaerobic bacteria of the genus Actinomyces. It is a rare and slowly progressive infectious disease affecting various organ systems, including the lung. Given its nonspecific clinical and radiological presentation of pulmonary form, the condition can simulate lung tuberculosis or malignancy. Thus it poses a diagnostic dilemma to the attending physician. Bacteriological culture studies and histological exams are diagnostic pillars that require specific attention to avoid misdiagnosis. It is often a treatable disease condition if diagnosed and treated early on.